How the Market Values Sustainability Performance? Studies in Indonesia and Japan - Duarmas, Maria Magdalena; Ekawati, Erni (Indonesian Journal of Sustainability Accounting and Management, 2024)
When earnings management practices are not disclosed properly, it can decrease value relevance of financial information. If earnings management is linked with profitability, its effect on decreasing value relevance becomes stronger. However, sustainability performance represented by ESG scores can have the opposite effect. This study aims to examine the effect of earnings management and value relevance, moderated by profitability and ESG scores. The samples used in this study are manufacturing companies listed on the Indonesia Stock Exchange and the Japan Stock Exchange in the period 2016-2019. Multiple regression analysis tests the hypothesis. The results indicate that earnings management has a negative and significant effect on value relevance in both Indonesia and Japan. Corporate performance measured by profitability can increase the negative effect of earnings management on value relevance, but sustainability performance measured by ESG scores can reduce the negative effect. The implication is that the marketplaces greater trust in companies that engage in ESG activities. As a trade-off, it is possible that ESG can be used to cover up these earnings management practices. This study contributes to adding evidence on the relationship between earnings management and value relevance, specifically when it is linked to profitability and ESG scores.